Collective action in canal irrigation systems management: the case of Doho Rice Scheme in Uganda - Sserunkuuma, Dick; Ochom, N.; Ainembabazi, John H. (International Food Policy Research Institute, 2004)
This brief is based on the results of a research project funded under the competitive grants program of the 2020 Vision Network for East Africa. A research report with the same title is available on IFPRI’s website (www.ifpri.org) and also upon request. Background Most of Uganda’s agriculture is rain-fed. Low and erratic rainfall is increasingly reducing crop yields and causing food insecurity. Irrigation is one option for enhancing agricultural production.